2011
DOI: 10.1007/s12088-011-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment of Dermatophytic Lesion on Mice (Mus musculus) Model

Abstract: Antidermatophytic potential of three weed plants viz. Tridax procumbens L., Capparis decidua (forsk) Edgew and Lantana camara L. were explored and experimentally induced dermatophytic lesion was topically treated in mice. Microbroth dilution method was carried out for determination of MIC and MFC of different extracts of selected plants. In animal studies, mice were experimentally inoculated with Trichophyton mentagrophytes and infected animals were topically treated with 5 mg/g terbinafine and two concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Apart from tannins, good antifungal activity is also shown by flavonoids. Bound flavonoids from roots of Lantana camara L. showed antifungal activity in studies on mice infected with Trichophyton mentagrophytes [ 287 ]. Complete recovery after application of the extract was observed after 16 days (drug reference after 12 days).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…Apart from tannins, good antifungal activity is also shown by flavonoids. Bound flavonoids from roots of Lantana camara L. showed antifungal activity in studies on mice infected with Trichophyton mentagrophytes [ 287 ]. Complete recovery after application of the extract was observed after 16 days (drug reference after 12 days).…”
Section: Skin Diseasesmentioning
confidence: 99%
“…13 14 Terbinafine has also been used systemically in the treatment of dermatophytosis in dogs and cats, 15 16 as well as in the treatment of canine Malassezia dermatitis. [17][18][19] In addition, topical terbinafine has been used successfully to treat dermatophytosis in mice, 20 and in a guinea pig model. 21 Of note, Sagit and others, 22 report no toxicity to the middle ear of rats when terbinafine was applied intratympanically.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings on experimentally induced dermatophytic lesion in mice reported by Sharma et al .,[ 7 ] indicate that T. Procumbens plant extract is an excellent topical antifungal agent for the cure of dermatophytosis. This plant also known to have antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%